Antimicrobial Activity of Stenochlaena palustris and Sauropus androgynus in Staphylococcus aureus, Escherichia coli and Candidia albicans - Budiarti, Lia Yulia; Isnaini, Isnaini; Dayana, Puteri; Sari, Norma; S., Nur Almira R. (Bioinformatics and Biomedical Research Journal, 2021)
Stenochlaena palustris and Sauropus androgynus are known to contains antimicrobial substances such as flavonoids, saponins and tannins compounds.The purpose of this study was to analyzes the antimicrobial activity of young and old leaf infusions of S. palustris and S. androgynus leaves against Staphylococcus aureus, Escherichia coli and Candida albicans. Analyze the antibacterial activity of a single preparations with a combination preparation of S.palustris (SP) and S.androgynus (SA) leaves infusion against S.aureus, E.coli and C.albicans. Leaves of S.palustris young part (SP1) taken 0-10 cm from shoots and old parts (SP2) 11-20 cm from shoots, while leaves of S.androgynus young part (SA1) leaves number 1 - 10 from the top and the old part (SA2) leaves number 11-20 from the top. The results showed that a single infusion of SP1 75% and SP2 75%, SA1 90% and SA2 90%, and a combination of SP1 75% and SA1 75%, SP2 75% and SA2 75% have the same activity as ampicillin in S.aureus. Single infusion of SP1 90% and SP2 90%, SA1 90% and SA2 90%, combination of SP1 75% and SA1 80% and the combination of SP2 80% and SA2 60% have the same activity as ciprofloxacin in E. coli. Single infusion of SP1 90% and SP2 90%, and a combination of SP1 80% and SA1 80%, SP2 80% and SA2 80% have the same activity as ketoconazole in C.albicans. The difference in activity due to differences in leaf parts used only occurred in E. coli, whereas in S.aureus and C.albicans (p <0.05).